Purification and characterization of Malaysian Mahseer (Tor tambroides bleekers) vitellogenin - Muhammad, Nurul Ashikin (2013)
Vitellogenin (vtg) is a high molecular weight glycophospholipoprotein synthesized in the liver under stimulation of estrogen. Basically found in sexually mature female,vtg is taken up by developing oocytes during maturation. It functions as a nutrient storage for growing embryo. Vtg has the potential as a maturation indicator for the successful production of fish fry. Tor tambroides is one of the most sought after fish in Malaysia, used as a game fish and economically important as cultured species. Main problem in the mass production of T. tambroides fry in hatchery is in the availability and selection of matured broodstock. Identification of matured and ready females morphologically can only be done by experience workers. Therefore,establishment of simple technique to identify matured females is necessary. Hence,in this current study, enzyme linked immunosorbent assay (ELISA) has been developed to measure blood plasma vtg as female maturation indicator. The development of this indicator will definitely contribute to the hatchery production of T. tambroides fry. Estrogen (17β-estradiol) was injected intra-peritoneally into five males (1.5 ±0.4kg).In order to confirm the synthesis of vitellogenin, raw plasma from E2-treated male, vitellogenic female and non-treated male were subjected to SDS-PAGE analysis.The presence of 149kDa protein band in E2-treated male plasma indicated the secretion of vitellogenin. Plasma samples were purified by size exclusion chromatography to separate protein particles according to molecular sizes. Fractions containing the bell-shaped major peaks were collected and subjected to native PAGE. Molecular weight of protein bulk was determined as 700kDa band. Further reduction of the protein bulk by SDS-PAGE resulted in the appearance of protein bands with similar positions in E2-treated sample and female whereas nontreated male showed no similarity. Specificity of antibody in Western blot revealed that in purified E2-treated male plasma, only three bands (133kDa, 117kDa, 56kDa) were recognized by anti-carp monoclonal antibody and thus identified as vtg. Bands with similar positions were also detected in mature female plasma. Male plasma did not show any cross reactivity against antibody. Enzyme-linked immunosorbent assay (ELISA) was developed for measurement of vtg concentration at plasma level. Purified vtg (253 ng/ml) was coated on 96-well microplate. Plasma samples were diluted with 1:500 antiserum to a final dilution of 1:1000. Linearization of binding displacement curves by logit transformation revealed that serial dilutions of mature female mahseer plasma slope was not statistically different from purified vtg of mahseer standard (F0.05=1.678 (12,28),p>0.05). ELISA assay developed for T. tambroides vitellogenin was confirmed through inter- and intra-assay validation. At different binding percentages (20, 50 and 80%), the coefficient of variation (CV%) of both precision assays (inter- and intra-assay) were less than 15% which means ELISA developed for the measurement of plasma vtg concentration in T. tambroides is sensitive and repeatable.